Financial Feasibility of Patin Fish Fillet Processing Business in Belitang District, East OKU Regency - Nasir Nasir; Leni Sabrina (Journal of Global Sustainable Agriculture, 2024)
This research aims to: 1) Calculate the investment value and operational costs, receipts and income of the catfish fillet processing business, and 2) Analyzing the financial feasibility of the catfish fillet processing business. The research was carried out in Belitang District, East OKU Regency, South Sumatra Province from July to August 2023. The population in this study were owners/managers of fish fillet making businesses, 12 fish farmers. This research uses a survey method.  The data collected consists of primary and secondary data. Sampling uses a saturated sampling method. Data collection was carried out using direct interviews with fish fillet processing industry players and catfish cultivating farmers. The data processing method uses quantitative analysis by calculating investment, operational, income and revenue costs. Financial feasibility is carried out through NPV, IRR, B/C Ratio and Payback Period analysis.  The research results provide conclusions: 1) The fish processing business is profitable in both the long term (10 years and the short term (1 year). During the economic life period (10 years), the total revenue is IDR 60,793,991,291.41,-, the total costs incurred are IDR 44,786,986,293.77 (investment costs IDR 1,781,010,000,- and operational costs IDR 43,005,976,293) so that income net IDR 16,007,004,997.64,-.  In the first (1st) year, total revenues were IDR 6,804,000,000,-, total costs IDR 6,013,629,500,- (investment depreciation costs IDR 148,417,500,- and operational costs IDR 5,865,212,000,-) so that income net amounting to IDR 790,370,500,- 2) The catfish fillet processing business is feasible to carry out with an NPV value of IDR 16,007,004,997.64, a B/C value of 0.35 and an R/C of 1.35, an IRR value of 82.09% and an investment payback period of 1.9 years  (1 year, 10 months and 4 days).